2021
DOI: 10.3390/nu13041043
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s Hard to Make Good Choices and It Costs More’: Adolescents’ Perception of the External School Food Environment

Abstract: Research on the impact of school and community food environments on adolescent food choice is heavily reliant on objective rather than subjective measures of food outlets around schools and homes. Gaining the perspective of adolescents and how they perceive and use food environments is needed. The aim of this study was to explore adolescent’s perception and use of the food environment surrounding their schools. Purposive sampling was used to recruit schools. Mapping exercises and discussion groups were facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…Food intake, mainly ultraprocessed foods, from outside of home increases with age [30,31]. The cost and convenience of the external school food environment are key factors influencing adolescents' food choices [32]. Our data also revealed that food-insecure adolescents reported a higher percentage of hunger than food-secure adolescents (5.1% vs. 0.3%) due to a shortage of allowance to purchase food.…”
Section: Discussionmentioning
confidence: 61%
“…Food intake, mainly ultraprocessed foods, from outside of home increases with age [30,31]. The cost and convenience of the external school food environment are key factors influencing adolescents' food choices [32]. Our data also revealed that food-insecure adolescents reported a higher percentage of hunger than food-secure adolescents (5.1% vs. 0.3%) due to a shortage of allowance to purchase food.…”
Section: Discussionmentioning
confidence: 61%
“…Children between 6 and 12 years subjectively chose, within their knowledge, foods with low nutritional value from school canteens ( 71 , 72 ) whereas socioeconomic factors played a major role in food choices when individuals were aged 30 years ( 73 ). University student population are transforming from low- to high-nutrition value preferences but limited by costly healthy food options ( 74 , 75 ). Before cost efficiency dominates dietary behavior in later adulthood, university students are susceptible to respond to interventions and adopt healthier dietary styles before they lose interest in considering nutritional value of their food and drinks.…”
Section: Discussionmentioning
confidence: 99%
“…The affordability of more expensive, healthier food options is a concern for adolescent consumers, with convenience and the cost of different foods acting mostly as a barrier for healthy food choices (13,42,74,79,81,87,93) . Adolescents tend to have busy schedules, with high demands from school, sports or recreational activities and their social lives, causing them to favour quick, easy-to-prepare foods that need little to no cooking or clean-up (13,42,81,89) .…”
Section: Barriers and Facilitators For Healthy Food Choice In Adolesc...mentioning
confidence: 99%
“…Data from the FCQ show that price and convenience regularly combine in their influence on adolescent food choices, appearing in the top three motivating factors throughout the research (Table 2) (7478) . Where there are healthy convenience foods available, these foods are often outside the budget of adolescents, particularly younger adolescents (79) . Individual financial constraints can determine adolescents' food choices when they are buying their own foods, and value for money is noted as a concern for adolescents, with many food choices being made on ‘meal deals’ or special offers on foods (79) .…”
Section: Barriers and Facilitators For Healthy Food Choice In Adolesc...mentioning
confidence: 99%
See 1 more Smart Citation